Pengaruh Profitabilitas, Likuiditas, Leverage Dan Corporate Governance Terhadap PengungkapanFinancial Distress Perusahaan Manufaktur Makanan & Minuman Serta Peralatan Rumah Tangga Yang Terdaftar Di Bei Tahun 2010-2015 - Nurmayanti, Novia; , Wiyadi, Drs.,M.M (2017)
Financial distress is a state of financial difficulties that occurred before the company went bankrupt. This study aimed to describe and analyze the effect of profitability (return on total assets), liquidity (current ratio), leverage (debt to equity ratio), and the corporate governance of the financial distress of companies manufacturing food and beverage sector and the sector of household appliances listed in the Indonesia Stock Exchange in the period 2005-2010. Purposive sampling method used as a method of determining the sample, and obtained a sample of 34 companies. Data analysis technique used is multiple linear regression analysis. Based on the research results show that profitability has a positive and significant impact on the financial distress and leverage a significant negative effect on the financial distress. While the mechanism of corporate governance, and liquidity does not have a significant effect on the financial distress.